An effective diagnostic strategy for accurate detection of RhD variants including Asian DEL type in apparently RhD‐negative blood donors in Korea. Issue 4 (19th October 2016) - Seo, M. H.; Won, E. J.; Hong, Y. J.; Chun, S.; Kwon, J. R.; Choi, Y. S.; Kim, J. N.; Lee, S. A.; Lim, A. H.; Kim, S. H.; Park, K. U.; Cho, D.
Abstract : Background and Objectives: The purpose of this study was to provide an effective RHD genotyping strategy for the East Asian blood donors. Material and Methods: RhD phenotyping, weak D testing and RhCE phenotyping were performed on 110 samples from members of the RhD‐negative club, private organization composed of RhD‐negative blood donors, in the GwangJu‐Chonnam region of Korea. The RHD promoter, intron 4, and exons 7 and 10 were analysed by real‐time PCR. Two nucleotide changes (c.1227 G>A, and c.1222 T>C) in exon 9 were analysed by sequencing. Results: Of 110 RhD‐negative club members, 79 (71·8%) showed complete deletion of the RHD gene, 10 (9·1%) showed results consistent with RHD‐CE‐D hybrid, and 21 (19·1%) showed amplification of RHD promoter, intron 4, and exons 7 and 10. Of the latter group, 16 (14·5%) were in the DEL blood group including c.1227 G>A ( N = 14) and c.1222 T>C ( N = 2), 2 (1·8%) were weak D, 1(0·9%) was partial D, and 2 (1·8%) were undetermined. The RhD‐negative phenotype samples consisted of 58 C‐E‐c+e+, 19 C‐E+c+e+, 3 C‐E+c+e‐, 21 C+E‐c+e‐, 6 C+E‐c+e+ and 3 C+E‐c‐e + . Notably, all 58 samples with the C‐E‐c+e+ phenotype were revealed to have complete deletion of the RHD gene. The C‐E‐c+e+ phenotype showed 100% positive predictive value for detecting D‐negative cases. Conclusions: RHD genotyping is not required in half of D‐negative cases. We suggest here an effective RHD genotyping strategy for accurate detection of RhD variants in apparently RhD‐negative blood donors in East Asia.